2021
DOI: 10.1139/cjfr-2020-0156
|View full text |Cite
|
Sign up to set email alerts
|

Water budget fluxes in catchments under grassland and Eucalyptus plantations of different ages

Abstract: The area with planted forests increased in the last decades and they have an important role in programs to sequester carbon. However, the effects of eucalyptus plantations on water resources in the Southern Grasslands biome are largely unknown, and we herein address water budget fluxes including green and blue flows. We evaluated green (canopy interception and evapotranspiration) and blue (discharge) water flows in three watersheds; two predominantly covered with Eucalyptus, either in the first years after pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
0
15
0
2
Order By: Relevance
“…Soil and forest/grassland management should be oriented towards protecting or restoring soil moisture and manage the green water flux for increased water productivity. An improved soil structure allows for increased infiltration and retention in the soil (Cavalli et al, 2020;Ferreto et al, 2020).…”
Section: Land Use and Management Implications For The Pampa Biomementioning
confidence: 99%
See 2 more Smart Citations
“…Soil and forest/grassland management should be oriented towards protecting or restoring soil moisture and manage the green water flux for increased water productivity. An improved soil structure allows for increased infiltration and retention in the soil (Cavalli et al, 2020;Ferreto et al, 2020).…”
Section: Land Use and Management Implications For The Pampa Biomementioning
confidence: 99%
“…Under extensive livestock production, the farming system has low productivity per animal and per area because of low forage availability where livestock is obliged to walk long distances in search of forage and water. The natural soil fragility combined with overgrazing has led to intense soil degradation by soil erosion (Roesch et al, 2009;Reichert et al, 2016;Ebling et al, 2020;Ferreto et al, 2020;Valente et al, 2020), and loss of soil carbon and grassland species diversity (Overbeck et al, 2007). Intense grazing and trampling by cattle cause soil compaction (Collares et al, 2011;Cecagno et al, 2016;Ambus et al, 2018), through an increase in the soil bulk density and a decrease in porosity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the wetter-than-normal year, streamflow was 66% lower in the eucalyptus than in the grassland, while evapotranspiration was 27% greater in E. saligna than in grassland catchment and groundwater recharge was 46% greater. From 2014to 2018, Ferreto et al (2021a observed that specific discharge was lower in E. saligna by 44-58% and in E. benthamii by 16-78% compared with grassland.…”
Section: Stream Discharge and Sediment Yield (From The Data Set)mentioning
confidence: 99%
“…Furthermore, study approaches used for agricultural crops can be adapted or improved for eucalyptus. In particular, opportunities are related to tillage in compacted areas by forest harvesting, by previously defining different soil compaction states in the field, such as performed for agricultural crops (Secco et al, 2009), considering spatial variability in soil physical properties (Silva et al, 2003;Marins et al, 2018); short-and long-term tillage (Veiga et al, 2008(Veiga et al, , 2009(Veiga et al, , 2010Reichert et al, 2016c) and cropping systems effects (Awe et al, 2015;Cecagno et al, 2016;Ambus et al, 2018;Reichert et al, 2022); refinement of plant available water as affected by soils and tillage, using existing pedotranfer functions (Vaz et al, 2005;Reichert et al, 2009Reichert et al, , 2020b or by developing improved ones, as well as via soil water balance (Reichert et al, 2021d), forest hydrology (Ferreto et al, 2021a) or catchment water-budget fluxes (Reichert et al, 2017bEbling et al, 2021;Ferreto et al, 2021b;Valente et al, 2021).…”
Section: Research Opportunitiesmentioning
confidence: 99%